The Near-Surface Small-Scale Spatial and Temporal Variability of Sensible and Latent Heat Exchange in the Svalbard Region: A Case Study. (19th July 2012) - Jocher, Georg; Karner, Florian; Ritter, Christoph; Neuber, Roland; Dethloff, Klaus; Obleitner, Friedrich; Reuder, Joachim; Foken, Thomas
Abstract : We present data from two eddy covariance systems for determining the sensible and latent heat flux and the shear stress near the earth's surface. One measures continuously since September 2010 close to the village Ny-Ålesund, Svalbard, the other one was located on Kongsvegen glacier for a short period in April 2011. Two examples for small-scale variability are discussed: near surface external gravity waves associated with katabatic wind from the Broggerbreen glacier located a few kilometres southwestern of Ny-Ålesund, and an episode when the two eddy systems at the different measurement sites captured very different conditions at the same time. In case of gravity wave motion the eddy covariance method results in fictitious positive fluxes due to the strong correlation between temperature and vertical wind, which has to be considered carefully. The comparison between the two sites showed that generally the dynamical processes near the Earth's surface for Ny-Ålesund and the Kongsvegen glacier are different and local. But there are also cases of synchronization due to synoptic influences, and then the same processes are visible at the two measurement sites. Both examples show that the boundary layer in Ny-Ålesund is not only affected by the main glaciers in the east of the village, but also by other orographical characteristics and synoptic issues. Therefore, the only meaningful way to deal with point measurements is to consider them in context with the surrounding orography and the general meteorological conditions.